Effect of pre-stroke statin use on stroke severity and early functional recovery: a retrospective cohort study - Choi, Jay Chol (BMC Neurol, 2015)
BACKGROUND: Experimental studies suggest that pre-stroke statin treatment has a dual effect of neuroprotection during ischemia and neurorestoration after ischemic injury. The aim of this study was to evaluate the effect of pre-stroke statin use on initial stroke severity and early clinical outcome. METHODS: We used a prospective database enrolling patients with acute ischemic stroke from 12 hospitals in Korea between April 2008 and January 2012. Primary endpoint was the initial stroke severity as measured by the National Institutes of Health Stroke Scale (NIHSS) score. Secondary endpoints were good outcome (modified Rankin Scale [mRS], 0–2) and overall mRS distribution at discharge. Multivariable regression model and propensity score (PS) matching were used for statistical analyses. RESULTS: Among the 8340 patients included in this study, 964 patients (11.6 %) were pre-stroke statin users. The initial NIHSS score (mean [95 % CI]) was lower among pre-stroke statin users vs. non-users in multivariable analysis (5.7 [5.2–6.3] versus 6.4 [5.9–6.9], p = 0.002) and PS analysis (5.2 [4.7–5.7] versus 5.7 [5.4–6.0], p = 0.043). Pre-stroke statin use was associated with increased achievement of mRS 0–2 outcome (multivariable analysis: OR [95 % CI], 1.55 [1.25–1.92], p < 0.001; PS matching: OR [95 % CI], 1.47 [1.16-1.88]; p = 0.002) and favorable shift on the overall mRS distribution (multivariable analysis: OR [95 % CI], 1.29 [1.12-1.51], p = 0.001; PS matching: OR [95 % CI], 1.31 [1.11-1.54]; p = 0.001). CONCLUSIONS: Pre-stroke statin use was independently associated with lesser stroke severity at presentation and better early functional recovery in patients with acute ischemic stroke. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12883-015-0376-3) contains supplementary material, which is available to authorized users.